Reasons for drug abuse and expenditures - Guedda, Hamza; Salhi, Elhoucine; Djeghel, Laid (جامعة الوادي - University of Eloued, 2023)
This intervention aims to give a clear reading of the most important reasons leading to drug use and the theories explained to it, as the drug use phenomenon is one of the biggest problems facing society, so knowing the causes of some people using drugs is very important, which is the starting point for following any interpretative procedure then It is followed by a preventive and remedial procedure, and in order to understand this problem deeply and objectively, and to know its causes, we must move away from unilateralism in the interpretation of this phenomenon, Many studies have resulted in it being a multidimensional problem and variables. There is no single theory, one factor or a specific variable, in the light of which the causal use of drugs can be explained as the factors multiply, and their importance varies from one society to another, so we will present in this intervention a set of causes and a set of Theories have provided explanations regarding the causes of widespread and widespread drug use in societies.. تهدف هذه المداخلة إلى إعطاء قراءة واضحة لأهم الأسباب المؤدية لتعاطي المخدرات والنظريات المفسرة لها, إذ تعد ظاهرة تعاطي المخدرات مشكلة من أكبر المشكلات التي تواجه المجتمع، لذلك فإن معرفة أسباب تعاطي بعض الأشخاص للمخدرات أمر في غاية الأهمية، وهو نقطة البداية لإتباع أي إجراء تفسيري ثم يتبعه الإجراء الوقائي والعلاجي, ولكي نفهم هذه المشكلة فهما عميقا وموضوعيا، ومعرفة أسبابها، وجب علينا أن نبتعد عن الأحادية في تفسير هذه الظاهرة، فالعديد من الدراسات أسفرت على أنها مشكلة متعددة الأبعاد والمتغيرات، فلا توجد نظرية واحدة أو عامل واحد أو متغير بعينه، يمكن في ضوئه تفسير سببية تعاطي المخدرات حيث تتعدد العوامل، وتتباين أهميتها من مجتمع لآخر, لذا سوف نعرض في هذه المداخلة جملة من الأسباب ومجموعة من النظريات قدمت تفسيرات تتعلق بأسباب تفشي وانتشار تعاطي المخدرات في المجتمعات.
الأسباب المؤدية لتعاطي المخدرات والنظريات المفسرة لها
article
Keywords: Drugs , explained theories , addiction , abuse; المخدرات ، النظريات المفسرة ، الإدمان ، التعاطي